To solve the quadratic equation \(3x^2 - 42x + 135 = 0\) by completing the square, follow these steps:
-
Move the constant to the other side of the equation: \[ 3x^2 - 42x = -135 \]
-
Divide the entire equation by 3 to simplify the leading coefficient of \(x^2\): \[ x^2 - 14x = -45 \]
-
Complete the square:
- Take half of the coefficient of \(x\) (which is -14), square it, and add to both sides.
- Half of -14 is \(-7\), and \((-7)^2 = 49\). \[ x^2 - 14x + 49 = -45 + 49 \] \[ x^2 - 14x + 49 = 4 \]
-
Rewrite the left-hand side as a squared binomial: \[ (x - 7)^2 = 4 \]
-
Take the square root of both sides: \[ x - 7 = \pm 2 \]
-
Solve for \(x\):
- For the positive root: \[ x - 7 = 2 \quad \Rightarrow \quad x = 9 \]
- For the negative root: \[ x - 7 = -2 \quad \Rightarrow \quad x = 5 \]
So the solutions to the equation \(3x^2 - 42x + 135 = 0\) are: \[ \boxed{5, 9} \]